2015
DOI: 10.1161/circ.132.suppl_3.9979
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 9979: Health-Related Quality of Life in Children With Marfan Syndrome

Abstract: Background: Marfan syndrome (MFS) is an autosomal dominant disorder that affects the heart, aorta, eyes, skeleton, lungs, and other organs. Objective: To assess quality of life (QL) in a large multicenter cohort of children with MFS. Methods: The Pediatric Quality of Life Inventory (PedsQL) was administered to 256 subjects with MFS ages 5-18 years as an ancillary study to the Pediatric Heart Network’s Marfan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…Surprisingly, no signi cant association was found between HRQoL and ocular impairment (ectopia lentis) whatever the severity, which is in line with other studies performed in children (19) and adults with MFS (7,8,13,17,18).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Surprisingly, no signi cant association was found between HRQoL and ocular impairment (ectopia lentis) whatever the severity, which is in line with other studies performed in children (19) and adults with MFS (7,8,13,17,18).…”
Section: Discussionsupporting
confidence: 89%
“…Only a few studies have evaluated HRQoL in the pediatric MFS population (19)(20)(21)(22). The results of these studies are sometimes divergent and di cult to compare notably because of differing scales used to measure HRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we directly measured child-reported ER-QOL and found scores were significantly lower across ‘bothered by eyes/vision’, ‘social’ and ‘frustration/worry’ domains compared with visually normal controls, confirming that children with lens dislocation experience a range of QOL concerns in their everyday life. Handisides et al have also reported lower overall, psychosocial and physical HRQOL among children and adolescents with MFS using the PedsQL Generic Core Scales 30. Notably, apart from MFS patients, there are still part of CEL children experiencing ocular and other systematic abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…9,10,12 In addition to accelerated vascular aging, MFS patients experience other age-related changes such as worsening of joint pain and stiffness, vision problems, hearing loss, skin elasticity, and lung complications. 1,2,[19][20][21] Evaluation of these aging-related characteristics requires further investigations, given that the mechanisms known to contribute to MFS-associated symptomology are also implicated in aging-related manifestations such as inflammation, ROS production, arterial remodeling, and elastolysis.…”
Section: Introductionmentioning
confidence: 99%